(3QSGdI Gdjef hgOGjI GdfahS GdWGgQGJ hde GdTed hLeY GdTJGJs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce GdefRg Yf GdPGJ hJhSdJ Edjg ai GdWGYI HhdjY GdbGFe GdeLGRGJ GdCee Ydi GdMSfGJ hGdSjFGJ s
(3BNQgG (B:s
(3aJjbXhG jG Cgd Gdjef aJGddg cCfce HGdcGFf bO cGf hGYJHQhG CjgG GdWgQI GdENhGf HeG ChVM dce ef GdBjGJ hGdHQgGf hGdMeO dehdGfG hMOg hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B60s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds